2022
DOI: 10.3389/fphys.2022.928195
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Metabolic Adaptations of Electrically Pulse-Stimulated Human Myotubes Using Global Analysis of the Transcriptome and Proteome

Abstract: Electrical pulse stimulation (EPS) has proven to be a useful tool to interrogate cell-specific responses to muscle contraction. In the present study, we aimed to uncover networks of signaling pathways and regulatory molecules responsible for the metabolic effects of exercise in human skeletal muscle cells exposed to chronic EPS. Differentiated myotubes from young male subjects were exposed to EPS protocol 1 (i.e. 2 ms, 10 V, and 0.1 Hz for 24 h), whereas myotubes from middle-aged women and men were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 79 publications
0
8
1
Order By: Relevance
“…Based on RNA-seq, we (18) and others (16,26) observed that processes related to cytokine and inflammatory pathways were upregulated after EL-EPS in C2C12 myotubes. Local inflammation plays a role in SkM adaptation to exercise (27).…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 94%
See 3 more Smart Citations
“…Based on RNA-seq, we (18) and others (16,26) observed that processes related to cytokine and inflammatory pathways were upregulated after EL-EPS in C2C12 myotubes. Local inflammation plays a role in SkM adaptation to exercise (27).…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 94%
“…Genes related to pro-inflammatory pathways were upregulated in myotubes originating from females with polycystic ovary syndrome relative to healthy controls (25). Although EL-EPS responses may be affected by donor characteristics (1,3), a recent study suggests that age, sex, and EL-EPS parameters may not have substantial transcriptomic and proteomic effects (26).…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies that used EPS as an in vitro model of exercise mimicking acute versus chronic or aerobic versus resistance training have mostly been described in the immortalized rodent cell lines C2C12 and L6 (24,25). From our review of the literature, 10 studies defined their EPS protocol as that of an "exercise-like" treatment on HSkMCs (26)(27)(28)(29)(30)(31)(32)(33), investigating exercise-mediated signaling mechanisms (26,(28)(29)(30)32,33), expression of mitochondrial-related genes (21,27,31), substrate metabolism (27,28,30,33,56), and measurements of mitochondrial quantity (27,28,(30)(31)(32)(33)) (Table ). No studies have investigated the impact of EPS on HSkMC mitochondrial respiratory capacity.…”
Section: Electrical Pulse Stimulationmentioning
confidence: 99%